In Vitro Resistance to Macrolides and Clindamycin by Group B Streptococcus Isolated from Pregnant and Nonpregnant Women. (20th May 2012) - Lambiase, Antonietta; Agangi, Annalisa; Del Pezzo, Mariassunta; Quaglia, Filomena; Testa, Antonio; Rossano, Fabio; Martinelli, Pasquale; Catania, Maria Rosaria
Abstract : Background . Despite the introduction of screening bases intrapartum prophylaxis, Streptococcus agalactiae is still an important etiological agent of perinatal infections. The increasing rate of resistance and the differences in resistance pattern among countries suggest that a program of surveillance at the institutional level is important in determining optimal prophylaxis. In contrast, knowledge on GBS epidemiology in Italy is limited, and no data are available in the Southern region of the country. We sought to determine the occurrence of resistance to macrolides and clindamycin of GBS isolates in pregnant and nonpregnant women. Methods . Between 2005 and 2008, 1346 vaginal and 810 rectovaginal swabs were obtained from pregnant and not-pregnant women. Results . The occurrence of macrolides and clindamycin resistance was 16.5% in 2005 increasing up to 69.9% in 2008. A high percentage of isolates was resistant to tetracycline through all the study period with no statistically significant annual. Conclusions . In our cohort, an increase of in vitro resistance of GBS to macrolides and clindamycin is clearly evident. The discordance with reports from different countries emphasize the crucial role of microbiological methods in setting possible therapeutic strategies.